TINGKAT PENGHIDUPAN MASYARAKAT DI LAHAN BERGAMBUT DESA JEJANGKIT TIMUR KECAMATAN JEJANGKIT KABUPATEN BARITO KUALA - Syarifuddin Syarifuddin; Herry Porda Nugroho Putro; Deasy Arisanty; Mohamad Zaenal Arifin Anis (Universitas Lambung Mangkurat, 2021)
The purpose of the research is to identify the livelihoods of the people in the peatland area and to identify the factors that influence the livelihoods of the people in the peatland area. The method in this research is quantitative, the data used in the study is primary data, namely from insights and questionnaires and secondary data in the form of documents. Collecting data using survey methods and questionnaires. The number of respondents as many as 87 household heads divided into 9 RTs, then analyzed by classifying index values and factor testing using SPSS, from the results of the factor test obtained information about the factors that most influence the livelihoods of people on peatlands. The results showed that there were differences in the level of livelihood, namely low, medium and high. The level of livelihood in Jejangkit Village is classified as moderate based on its index value. There are 2 dominant factors that influence, namely the main factor (social assets, human resources and activities) and financial asset factors.